2009
DOI: 10.1136/hrt.2008.157727
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognised myocardial infarction in subjects at high vascular risk: prevalence and determinants

Abstract: In cardiac asymptomatic subjects at high vascular risk, UMI is common. The risk of UMI increases with increasing presence of risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…We thank Dr Jolobe for his interest in our article 1. As mentioned by Dr Jolobe,2 previous studies have indeed reported an association between left bundle branch block (LBBB) and myocardial infarction.…”
mentioning
confidence: 83%
“…We thank Dr Jolobe for his interest in our article 1. As mentioned by Dr Jolobe,2 previous studies have indeed reported an association between left bundle branch block (LBBB) and myocardial infarction.…”
mentioning
confidence: 83%
“…To the editor: Although the prevalence of left bundle branch block (LBBB) was not documented in the evaluation of unrecognised myocardial infarction (MI) in subjects at high vascular risk,1 one study demonstrated that 47% of 29 585 patients with LBBB and MI presented without chest pain 2. Accordingly, there is a huge potential for under-recognition of MI in the subgroup of patients with LBBB who present without chest pain.…”
mentioning
confidence: 99%
“…Accordingly, there is a huge potential for under-recognition of MI in the subgroup of patients with LBBB who present without chest pain. The potential for under-recognition of MI in LBBB is compounded by the fact that diabetes mellitus, an acknowledged risk factor for LBBB,3 is, in its own right, associated with an odds ratio of 1.93 (confidence interval 0.93 to 3.99) for risk of unrecognised MI 1. The association between diabetes, LBBB and coronary heart disease (CHD) comes from a study in which diabetes was documented in 22% of 116 subjects with angiographically proven CHD 3.…”
mentioning
confidence: 99%
“…This technique is also called late gadolinium-enhanced MRI (LGE-MRI), myocardial delayed enhanced (MDE) MRI and delayed hyperenhanced MRI (DHE-MRI) in the literature. DE-CMR has been shown to be more sensitive than other imaging methods in detecting small subendocardial infarctions [1] and has recently been used in population-based studies to assess the presence of myocardial scar [2,3]. The technique is relatively straightforward to implement, and images can be interpreted visually for the presence of myocardial scar (hyperenhanced region) without the need for post-processing.…”
mentioning
confidence: 99%